MEMBANGUN BRAND DESTINATION PASIR KUNCI SEBAGAI TUJUAN WISATA DI KOTA BANDUNG - Faizal Hamzah; Yosef Abdul Ghani; Topan Taufik Faturochman (Jurnal Sains Manajemen, 2022)
Pasir Kunci tourist attraction is located in Pasir Kunci village of Pasir Jati village, Ujungberung district of Bandung. This tourist attraction is a cultural attraction, but less well known by the public at large. In addition, the supporting facilities of Pasir Kunci tourist attraction as a cultural tourism are not adequate. Where as if managed well and has been known by the public at large, this tourist attraction has the potential to become one of the leading tourist attractions in the city of Bandung. One of the efforts to develop a marketing process that has not been maximized is to design the Pasir Kunci brand destination as a cultural tourism destination in the city of Bandung. This research aims to formulate the stages of building a brand destination Pasir Kunci as a cultural tourism destination in the city of Bandung. The method used in this study is a qualitative descriptive method that is then analyzed using SWOT analysis. Data collection techniques in this study are obtained through interview activities, direct observation at the tourist attraction in question, and documentation. The results of this research are obtained a strategy in building a brand destination of Pasir Kunci as a cultural tourism destination in the city of Bandung among others, developing virtual tourism, developing the potential of Pasir Kunci attractions, creating creative content and promoting through social media